The Influence of Remote Work Flexibility, Digital Leadership, Employee Engagement, and Work-Life Balance on Organizational Commitment in Hybrid Work Environments - Chairul Hakim; Joko Ariawan; Inganatul Khasanah; Noorhani Dyani Laksmi (Malaqbi Publisher, 2026)
The rapid adoption of hybrid work environments has transformed organizational practices and employee experiences, requiring a deeper understanding of the factors that influence organizational commitment. This study aims to examine the influence of remote work flexibility, digital leadership, employee engagement, and work-life balance on organizational commitment in hybrid work settings. Using a quantitative approach with a cross-sectional survey design, data were collected from employees working under hybrid systems and analyzed using Structural Equation Modeling (SEM). The findings reveal that all four variables have a positive and significant effect on organizational commitment. Among them, employee engagement emerges as the strongest predictor, followed by work-life balance, digital leadership, and remote work flexibility. These results indicate that while structural factors such as flexibility and leadership are important, psychological and well-being factors play a more dominant role in fostering employee commitment. The study highlights the importance of integrating flexible work arrangements with supportive leadership and employee-centered practices to enhance engagement and work-life balance. This research contributes to the literature by providing a comprehensive framework for understanding organizational commitment in hybrid work environments and offers practical implications for organizations seeking to improve employee retention and performance in the modern workplace.